1997
DOI: 10.5962/bhl.title.50157
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of ingested bismuth alloy shot in game-farm mallards

Abstract: We detected no effects on game-farm mallards of dosing with 6 No.4 Bi shot or 6 No. 4 Fe shot, as compared with 0-dosed (control) ducks and with each other, on survival to 30 days post dosing, Hct values, body weight, or in the mean weights of kidneys, livers, gonads, and gizzards. All 240 Bi-dosed shot (6 shot in each of 40 ducks) were probably retained during the study. As many as 10 of the 240 Fe shot were probably dissolved, but they may have been voided. Dissolution rates for both Fe and Bi shot from DIy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 3 publications
3
19
1
Order By: Relevance
“…Heterophilias can be indicative of inflammatory diseases as well as toxicities, and are often the cause of leucocytosis, the magnitude of which often reflects the extent of the inflammatory response (Campbell, 1994). The slight heterophilia observed in control ducks was consistent with the mild inflammatory changes considered normal for farm-raised mallards (Sanderson et al, 1997b). Marked heterophilia in Zn-dosed ducks was consistent with the gastrointestinal lesions observed in this study, as well as gross and microscopic lesions reported by Levengood et al (1999) for mallards dosed with six Zn shot pellets of the same size and composition.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Heterophilias can be indicative of inflammatory diseases as well as toxicities, and are often the cause of leucocytosis, the magnitude of which often reflects the extent of the inflammatory response (Campbell, 1994). The slight heterophilia observed in control ducks was consistent with the mild inflammatory changes considered normal for farm-raised mallards (Sanderson et al, 1997b). Marked heterophilia in Zn-dosed ducks was consistent with the gastrointestinal lesions observed in this study, as well as gross and microscopic lesions reported by Levengood et al (1999) for mallards dosed with six Zn shot pellets of the same size and composition.…”
Section: Discussionsupporting
confidence: 91%
“…Diet, including ingestion of soil and grit, can have a dramatic effect on Pb shot erosion and Pb absorption, retention, and excretion rates, and can be important in mitigating the toxic effects of ingested Pb (Sanderson and Bellrose, 1986). Dietary components such as calcium (Ca), phosphorus (P), and protein, along with the size and hardness of food items, are important in determining the susceptibility of ducks to lead poisoning through the ingestion of Pb shotshell pellets (Jordan, 1968;Sanderson and Bellrose, 1986). Evidence indicates that lead-poisoned ducks may select a diet that may help alleviate lead toxicosis (Jordan, 1968).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bell et al (1965) and Sturkie (1976) reported that lowered hematocrit was associated with egg production in birds. Similar results were reported by Sanderson et al (1997) in that female mallards repeatedly dosed with eight #4 bismuth alloy shot had a decline in average hematocrit during reproduction. Tungsten has been shown to have no effect on hematocrit in short-term studies (辖32 days) using game-farm mallards (Ringelman et al, 1993;Kelly et al, 1998).…”
Section: Discussionsupporting
confidence: 88%
“…Some toxicity studies showed that Bi as one of the least harmful metals to human and wild animal life [13][14][15][16]. Others suggested that more experimental evidences are needed on the environmental behavior and toxicity of Bi [4,17].…”
Section: Introductionmentioning
confidence: 99%